Top

Equivalent Expressions Calculator
Top
Equivalent expression is said to be equivalent if two algebraic expressions are equalized by substituting the values of the variables. We use the symbol “ = “ or “ $\equiv$ “ to denote the equivalent expression.

Equivalent Expressions Calculator is used to find the equivalent expressions when two algebraic expressions are equivalent.

An expression is given below as a default input for this calculator. By applying distributive property and expanding the expression, get the simplified expression on clicking "Submit".

## Step by Step Calculation

Step 1 :

Observe the given expressions and expand the expression using distributive property.

Step 2 :

Simplify the expression to get the answer.

## Example Problems

1. ### Find the equivalent expression for this: 3y(x + 9)

Step 1 :

The given algebra expression is 3y(x + 9)

Now we need to expand by applying distributive property.

Step 2 :

So, 3y(x + 9) = 3y • x + 3y • 9

= 3xy + 27y

Therefore, 3y(x + 9) $\equiv$ 3xy + 27y.

3xy + 27y.

2. ### Find the equivalent expression for this: (x + 4)(x + 3)

Step 1 :

The given algebra expression is (x + 4)(x + 3)

Now we need to expand by applying distributive property.

Step 2 :

So, (x + 4)(x + 3) = x • (x + 3) + 4 • (x + 3)

= x • x + x • 3 + 4 • x + 4 • 3

= x2 + 3x + 4x + 12

= x2 + 7x + 12

Therefore, (x + 4)(x + 3) $\equiv$ x2 + 7x + 12.